2012
DOI: 10.1142/s0218196712500610
|View full text |Cite
|
Sign up to set email alerts
|

Context-Free Rewriting Systems and Word-Hyperbolic Structures With Uniqueness

Abstract: This paper proves that any monoid presented by a confluent context-free monadic rewriting system is word-hyperbolic. This result then applied to answer a question asked by Duncan & Gilman by exhibiting an example of a word-hyperbolic monoid that does not admit a word-hyperbolic structure with uniqueness (that is, in which the language of representatives maps bijectively onto the monoid). ment through the FCT (Fundação para a Ciência e a Tecnologia) under the project PEst-C/MAT/UI0144/2011 and through an FCT Ci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…For automatic semigroups, it is possible to assume that the automatic structure has a further pleasant property, namely that every element of the semigroup is represented by a unique word in the language of representatives [KO06, Proposition 2.9(iii)]. However, there exist word-hyperbolic semigroups (indeed, word-hyperbolic monoids) that do not admit word-hyperbolic structures where the languages of representatives have this uniqueness property [CM12,Examples 10 & 11].…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…For automatic semigroups, it is possible to assume that the automatic structure has a further pleasant property, namely that every element of the semigroup is represented by a unique word in the language of representatives [KO06, Proposition 2.9(iii)]. However, there exist word-hyperbolic semigroups (indeed, word-hyperbolic monoids) that do not admit word-hyperbolic structures where the languages of representatives have this uniqueness property [CM12,Examples 10 & 11].…”
Section: 13mentioning
confidence: 99%
“…This generalization has led to a substantial amount of research on word-hyperbolic semigroups; see, for example, [CM12,FK04,HKOT02,HT03]. Some of this work has shown that word-hyperbolic semigroups do not possess such pleasant properties as word-hyperbolic groups: they may not be finitely presented, and they are not in general automatic or even asynchronously automatic [HKOT02, Example 7.7 et seq.…”
Section: Introductionmentioning
confidence: 99%
“…Gray and Kambites were not the first to look for a notion of hyperbolicity for monoids but their notion is the first geometric one that takes directions into account. Previous definitions either were based on context-free rewriting systems, see e. g. [6,7,12,13,19], or looked at the underlying undirected graph of Cayley digraphs of semigroups, see e. g. [6,8,13]. Portilla et al [22] considered a notion of hyperbolicity in (a certain class of) digraphs that is also defined via hyperbolicity of their underlying undirected graphs.…”
Section: Introductionmentioning
confidence: 99%
“…When one generalizes from groups to semigroups, there is some geometry on Cayley graphs: for instance, there are several possible definitions of hyperbolicity for semigroups [6,9,15]; one can also define ends of finitely generated semigroups and prove results about them similar to those about ends of groups [23,24]. For This work was partially supported by the Fundação para a Ciência e a Tecnologia (Portuguese Foundation for Science and Technology) through the project UID/MAT/00297/2013 (Centro de Matemática e Aplicações).…”
Section: Introductionmentioning
confidence: 99%